Perkawinan Dalam Perspektif Tasawuf - Azhar Azhar; Putri Amelia (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
This dissertation discusses Marriage in the perspective of Sufism (Study of analysis of Legislation on Marriage in Indonesia). This is done considering the high divorce rate in Indonesia even though the legislation regarding marriage has been made quite a lot by the government and even the Marriage Law No. 1 of 1974 and the Compilation of Islamic Law have long been enacted. The purpose of this study is to find out why Islamic marriage regulations and legislation in Indonesia have not been able to stem the flow of divorce and family disharmony, and what solutions can be offered in minimizing divorce in Indonesia, as well as how to establish marriage law with the Sufism approach. The process of collecting data is done by means of library research (Library Research). The reading material is described and analyzed using qualitative methods so that the causes of the high divorce rate in Indonesia are found. After the discussion, two main problems were found, namely formal problems and non-formal problems. Formal problems are problems that are related to the rules and regulations of marriage itself. While non-formal problems are problems that arise from the personal members of each family. To overcome problems related to formal problems, the solution offered is the need to review several articles in the Marriage Law Number 1 of 1974 and need to revive the functions of the Marriage Advisory Counseling and Conservation Agency (BP4) as before the Marriage Law Number 1 year 1974. Meanwhile, to overcome problems related to non-formal problems, it is necessary to give Sufism teachings to the bride and groom who are delivered when they attend bride and groom courses organized by the Ministry of Religion throughout Indonesia. In order to establish marriage law with the Sufism approach, the connection between Sufism values and laws in the frame of benefit is needed. For this reason, the values of Sufism such as warak and zuhud and qonaah and so on need to be developed and integrated in connection with marriage law. The interconnection of the values of Sufism with marriage law is needed in numbers to minimize the divorce rate in Indonesia. Keywords: Marriage law, Sufism